Venho das águas: uma travessia autobiográfica nas culturas indígenas e formação docente - Anaquiri, Mirna Kambeba Omágua - Yetê (2022)
This research is organized in the form of narratives through which I describe my experiences as an indigenous woman, feminist, teacher, researcher, artist, and activist of the indigenous movement, belonging to the original Kambeba Omágua people, in the state of Amazonas (Amazon). The investigation intertwines, through autobiographical and narrative approaches, experiences that involve indigenous and quilombola women. The data produced in the field research was collected from the project Indigenous culture: A seed on the school floor. The project focuses on the challenge of thinking how my experiences can contribute to my practice as a teacher, as well as tothe training of other teachers. The project Indigenous culture: A seed on the school floor was carried out at the Benedito Soares de Castro Municipal School of Integral Time (Goiania, GO, Brazil) with ten professionals from basic education, eight women and two men. Dialogical problematizations and reflections grounded discussions and analyses anchored in the principles of visual culture education, questioning how information about indigenous culture reaches the school space, which images and visualities are present or absent and how they are utilized. In collaboration with the teachers that participated of the field research, the study investigated ways of thinking and pedagogically working on indigenous culture, identifying stereotypes, avoiding distortions and prejudices but, above all, recognizing the rights and respect for indigenous peoples